2009
DOI: 10.1111/j.1365-2982.2009.01387.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nadir lower oesophageal sphincter pressure on bolus clearance assessed by combined manometry and multi‐channel intra‐luminal impedance measurement

Abstract: This study aimed to assess the relationship between nadir lower oesophageal sphincter pressure (LOSP) and wave amplitude (WA) in oesophageal bolus clearance. Concurrent oesophageal manometry and impedance were performed in 146 subjects [41 healthy, 24 non-obstructive dysphagia (NOD) and 81 gastro-oesophageal reflux (GOR)]. Patients with achalasia and diffuse oesophageal spasm were excluded. Swallow responses were categorized by nadir LOSP. For each category of nadir LOSP, WA at the distal 2 recording sites wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
(94 reference statements)
0
9
0
Order By: Relevance
“…One possible explanation of this is that metrics which characterize features of the intrabolus domain are not well integrated into the present classification system. Bolus transit and clearance can be assessed with intraluminal impedance measurement . However, on its own, impedance measurement has failed to deliver the anticipated diagnostic gain in dysphagia, possibly because failed bolus clearance in itself occurs commonly in asymptomatic individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One possible explanation of this is that metrics which characterize features of the intrabolus domain are not well integrated into the present classification system. Bolus transit and clearance can be assessed with intraluminal impedance measurement . However, on its own, impedance measurement has failed to deliver the anticipated diagnostic gain in dysphagia, possibly because failed bolus clearance in itself occurs commonly in asymptomatic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Although an improved sensitivity to detect motor dysfunctions leading to abnormal bolus flow was expected with the use of HRM, a recent study showed that HRM based metrics were also poorly predictive of bolus transit failure, suggesting that manometry as a stand‐alone technique may not be sensitive enough to elucidate esophageal motility events underlying ineffective esophageal bolus clearance and/or dysphagia. Hence, the utility of combining the esophageal motility patterning with bolus flow using intraluminal impedance measurement was proposed and extensively used as a technique to assess bolus transport throughout the esophageal lumen and across the EGJ . However, to date, the combined manometry‐impedance technique, as routinely applied, yields little in terms of further diagnostic insights in patients presenting with dysphagia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manometric measurements The manometric recordings were analyzed manually to determine: (i) esophageal pressure wave amplitude and velocity, (ii) peristaltic success, and (iii) basal and nadir LES pressure. The definition of normal and various abnormal esophageal motility conditions have been previously reported 3,6,13 …”
mentioning
confidence: 99%
“…Previous studies using standard impedance-manometry recordings have shown that nadir lower esophageal sphincter (LES) pressure during swallowing has an impact on the propulsive force necessary for complete bolus transit, even within the normal range for swallow-induced LES relaxation [24]. This was particularly so for patients with nonobstructive dysphagia.…”
Section: Relationship Between Esophageal Peristalsis and Lower Esophamentioning
confidence: 99%